Using Virtual Reality to Improve Classroom Behavior in People With Down Syndrome: Within-Subjects Experimental Design - Stefan Carlo Michalski; Ancret Szpak; Caroline Ellison; Rowena Cornish; Tobias Loetscher (JMIR Publications, 2022)
BackgroundPeople with Down syndrome face various learning challenges. Introducing new and enjoyable experiences in learning settings may improve learning outcomes. Immersive and interactive technologies such as virtual reality can be used to deliver rich visual experiences in classrooms. ObjectiveThe aim of this study was to investigate the feasibility and benefits of virtual reality exposure for people with Down syndrome in learning settings. MethodsTo address this aim, we used a within-subjects design to assess the effect of a brief virtual reality drawing experience and conventional drawing experience on subsequent behavior in 16 participants. ResultsLarge positive effects were found for virtual reality drawing (t15=5.020, P<.001) and conventional drawing (t15=3.720, P=.002) in improving subsequent behavior in a learning setting. Irrespective of the intervention, the participant's mood, attention, and overall behavior significantly improved. No significant differences were found between the interventions (t15=-0.648; P=.53). ConclusionsThis study's results are encouraging for researchers and educators interested in using virtual reality for people with Down syndrome, as virtual reality was found to be highly feasible. Recommendations are made for researchers and educators interested in providing virtual reality experiences for people with Down syndrome.